PENGARUH KEPEMIMPINAN KERJA TERHADAP KINERJA MELALUI LOYALITAS KERJA DAN KOMITMEN ORGANISASI PADA DISPENDA PROVINSI RIAU - Aulia Safira; Susi Hendriani; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in DISPENDA Riau Province which is located at Jalan Jend Sudirman Pekanbaru. The purpose of this study was to determine the effect of leadership work against the loyalty of employees working on DISPENDA Riau province, determine the effect of leadership work on organizational commitment of employees in DISPENDA Riau province, determine the effect of leadership work on performance through the loyalty of employees working on DISPENDA Riau province, and to determine the effect leadership work on performance through organizational commitment of employees in DISPENDA Riau Province. Based on the research results show that (1) leadership influence on employee loyalty in DISPENDA Riau Province. The better the leadership exercised by the leadership it will increase the loyalty of employees working on the contrary if the leadership is done poorly it will lower employee loyalty; (2) leadership influence on organizational commitment of employees in DISPENDA Riau Province. The better the leadership exercised by the leader it will increase employee commitment to the organization done otherwise if the leadership is not good it will lower the organizational commitment of employees; (3) Leadership direct influence on employee performance DISPENDA Riau Province. Means the better the leadership exercised by the leader does not affect employee loyalty for leadership directly affects performance, not through job loyalty; and (4) leadership has direct influence on employee performance DISPENDA Riau Province. Means the better the leadership exercised by the leader does not affect organizational commitment of employees for leadership directly affects performance, not through organizational commitment.Keywords: Leadership Training, Performance, Loyalty Work, Organizational Commitment